Relationship between instructions and self-care behaviors of patients submitted to third molar extraction - Zerbetto, Marília Vieira; Faleiros, Pedro Bordini; de Moraes, Antonio Bento Alves (Perspectivas em Análise do Comportamento, 2018)
Dental surgeries can promote potential complications during and after the intervention at the time of recovery. The objective of the study was to identify the self-care behaviors of patients submitted to third molar extraction. Ten patients, aged between 18 and 24 years, participated in the study. After removal of the suture, participants were asked to individually answer questions from an interview script with questions regarding their experience with surgery and the recovery process. The analysis of the results allowed to identify three patterns of behavior among the participants, the first composed by those who emitted all behaviors oriented by the dentist surgeon; The second group consists of participants who initially followed the orientation and modified the way to perform self-care due to the permanence of the aversive event, or absence of it; The third, by participants who were not initially under the control of the dentist surgeon’s guidelines to issue self-care behaviors in the postoperative period, but throughout the recovery they began to emit such behaviors. The investigation of such a relationship based on the model selection by the consequences may be relevant for the analysis and promotion of self-care behaviors emitted by dental patients.